PENGEMBANGAN E-LKPD MATEMATIKA BERBASIS CTL MENGGUNAKAN LIVEWORKSHEET PADA SISWA KELAS VIII SMPN 13 MERANGIN - Desi Lasmira; Ferinaldi; Ade Susanti (Hiradika | Hira Institute, 2026)
Mathematics learning at SMP N 13 Merangin faces the problem of lack of teaching materials and the use of methods with textbooks that cause students to be less active and learning outcomes have not met the criteria for classical completeness. The purpose of this study is to produce E-LKPD based on Contextual Teaching and Learning using Liveworksheet that is valid, practical and effective. The development model used in this study is ADDIE with research subjects of grade VIII students. The research instruments include validation sheets, practicality questionnaires, student activity observation sheets, and learning outcome tests. The validation results by 5 validators, consisting of material, language, media, and practitioner experts, show an average validity score of 4.66 with a very valid category. The practicality aspect based on the practicality questionnaire obtained a percentage of 85.03% with a very practical category. Meanwhile, the effectiveness aspect is reviewed from student learning activities which reached 76.87% with an active category and the completeness of learning outcomes of 81% with an effective category. Thus, it can be concluded that the E-LKPD based on Contextual Teaching and Learning using Liveworksheets that was developed is valid, practical, and effective